Inter-country wage differences in the European Union - Pereira, João Manuel (2018)
This article investigates the determinants of wage gaps between European Union countries along the wage distribution, applying the methodology proposed by Firpo, Fortin and Lemieux (2009) and Fortin, Lemieux and Firpo (2011). The authors conclude that both wage structure and composition effects contribute to explaining wage differentials, but that the wage structure effect is more important. This latter effect would appear to derive from differences between unknown factors, while the composition effect can largely be explained by differences in the following areas: education, proportion of workers with supervisory responsibilities, occupational structure, and, to a lesser extent, industrial structure.